PENGARUH KUALITAS PELAYANAN DAN CUSTOMER EXPERIENCE TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Cafe Ruang Teduh) - Salsabila Putri Azahra; Sahara; Tedi Kustandi (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the effect of Service Quality (X1) and Customer Experience (X2) on Purchasing Decisions (Y) case study at Ruang Teduh Coffee. The method used in this study is a quantitative method. The population in this study is the number of visitors to Ruang Teduh Coffee for the period November 2024 to April 2025 with a population of 3,774 visitors. Determination of the number of samples taken as respondents in this study using the Slovin formula, the results of the calculation of sample data using the Slovin formula are 100 respondents. Sampling uses a non-probability sampling technique. The data collection technique uses a questionnaire. The data analysis technique used is multiple linear regression assisted by using IBM SPSS 22. The results of this study indicate that Service Quality has a positive and significant effect on Purchasing Decisions, Customer Experience has a positive and significant effect on Purchasing Decisions, Service Quality and Customer Experience together have a positive and significant effect on Purchasing Decisions.